2017
DOI: 10.1371/journal.pone.0178343
|View full text |Cite
|
Sign up to set email alerts
|

Associations between anthropometric parameters and lipid profiles in Chinese individuals with age ≥40 years and BMI <28kg/m2

Abstract: BackgroundLipid abnormalities are associated with overweight and obesity. Some simple anthropometric measurements such as body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHpR), and waist-to-height ratio (WHtR), may link to increased risk of dyslipidemia. However, diverse results were found in different population studies. We focused on the associations between these measurements and dyslipidemia in non-obese (BMI <28kg/m2) population aged more than 40 years.Methods and findingsCross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 27 publications
7
16
0
2
Order By: Relevance
“…It was indicated that body mass index (BMI) correlated positively with the levels of TC, TG and LDL-C, but negatively with HDL-C level [14]. It was also reported that increasing BMI increased risks for hypertriglyceridemia, high LDL-C and low HDL-C [15].…”
Section: Introductionmentioning
confidence: 99%
“…It was indicated that body mass index (BMI) correlated positively with the levels of TC, TG and LDL-C, but negatively with HDL-C level [14]. It was also reported that increasing BMI increased risks for hypertriglyceridemia, high LDL-C and low HDL-C [15].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the well-known notion that high BMI correlates with unfavorable lipid profile. [42,43] Levels of LDL-C and TG increased with age, in both males and females. However, the sex difference in the values of LDL-C and TG becomes insignificant in the oldest age group (≥ 55 years).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Yang and cols. (31) aimed to find the best anthropometric indicator to discriminate the dyslipidemia prevalent in a non-obese Chinese population aged over 40 years. The BMI showed a higher correlation with lipids than WC and waist/hip ratio, not only in the stepwise regression analysis, but also in logistic regression.…”
Section: Discussionmentioning
confidence: 99%